Dental Caries and Associated Factors Among Patients Attending the University of Gondar Comprehensive Hospital Dental Clinic, North West Ethiopia: A Hospital-Based Cross-Sectional Study - Teshome A; Andualem G; Derese K (Dove Medical Press, 2020)
Amare Teshome, Getaneh Andualem, Kirubel Derese Department of Dentistry, University of Gondar, Gondar, EthiopiaCorrespondence: Amare TeshomeDepartment of Dentistry, University of Gondar, Gondar, EthiopiaTel +251 910517002Email teferaden@gmail.comPurpose: Dental caries are an emerging public health problem in developing countries in the last two decades. However, there is a paucity of data on dental caries in northwest Ethiopia. This study investigated the prevalence of dental caries and associated factors in northwest Ethiopia.Patients and Methods: A hospital-based cross-sectional study was conducted in 368 patients who visited the University of Gondar Comprehensive Hospital Dental Clinic. A systematic random sampling technique was used to select the samples. Data were collected by three qualified dental surgeons using a pre-designed questionnaire modified from a WHO oral health survey and the clinical examination was done using the WHO dental caries diagnosis guideline. Data analysis was done using SPSS 20. Descriptive data were presented in tables and logistic regression analysis was done to identify the possible predisposing factors using odds ratios with 95% confidence interval.Results: The prevalence of dental caries in this study was 23.64% (95% CI: 19.30, 28.00) with a significant difference between females (30.56%) and males (17.02%). Being female (AOR=2.15 (95% CI: 1.31, 3.52), poor oral hygiene practice (AOR=2.44 (95% CI: 1.46, 4.07), being diabetic (AOR=8.15 (95% CI: 3.2, 20.75), low educational level (AOR=1.81 (95% CI: 1.05, 3.1), low monthly income (AOR=3.05 (95% CI: 1.54, 6.02) and halitosis (AOR=10.98 (95% CI: 5.68, 2.24) were significantly associated with dental caries. The mean DMFT score was 1.095± 0.24 (SD). The majority of the DMFT (70.59%) was due to decay, while filled tooth accounted for only 2.17% of the DMFT. The DMFT score was higher in females (0.625), urban residents (0.85), and those with montly income of ≤ 2500 Ethiopian birr (0.86). The mean DMFT was 0.13.Conclusion: The prevalence of dental caries in the study participants was 23.64% andwas higher in males than females and in diabetic patients. Female gender, poor tooth brushing habits, diabetes mellitus, and halitosis were significant predictors associated with dental caries.Keywords: dental caries, tooth decay, DMFT, predisposing factors, oral hygiene practice